Wife, mother, widow : exploring women's lives in Northern India - Wadley, Susan Snow 1943- (New Delhi : Chronicle Books ; Bangalore : Distributed by Orient Longman, 2008)
Study conducted at Karimpur, India.
Includes bibliographical references and index.
Keywords: Rural women -- India -- Karimpur -- Social conditions -- Case studies; Rural women -- India -- Karimpur -- Economic conditions -- Case studies